CONTRIBUTION TO HYDRAULIC CHARACTERISTICS OF PLIO-PLEISTOCENE DEPOSITS OF THRIASSION PLAIN OF ATTICA - Hermides, D.; Mimides, T.; Stamatis, G. (Bulletin of the Geological Society of Greece, 2016)
The geological structure of Thriassion Plain is generally complex and has been affected at different times by many tectonic activities. The last ones are the neotectonic, which caused horsts and grabens structures. Geologic and tectonic structures have influenced the hydrogeological conditions and the groundwater flow. Hydraulic characteristics of Plio-Pleistocene deposits differ throughout their extent. In this study, pumping tests in Plio-Pleistocene deposits are represented and the hydraulic characteristics transmissivity T, storativity S and hydraulic conductivity K are assigned. Pumping tests, in 8 totally wells, were conducted in the dry period. Methods as Cooper-Jacob’s, Theis’s, Papadopoulos Cooper’s and Neuman’s and last the Recovery method, are used to assign the hydraulic characteristics. These tests highlighted the Recovery method as the most reliable. Transmissivity T: 18-279.1 m2/d, storativity S: 2.5*10-3 3*10-2and hydraulic conductivity K: 0.4-25.1 m/d. Specific capacity is also determined ranging between 16-360 m3/d/m. This study contributes, essentially, in the approach of hydrogeological conditions of Thriassion Plain.